2014
DOI: 10.1248/cpb.c14-00109
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Vinyl Ketone, a Toxic Ingredient in Cigarette Smoke Extract, Modifies Glutathione in Mouse Melanoma Cells

Abstract: Cigarette smoke contains many harmful chemicals, which contribute to the pathogenesis of smokingrelated diseases such as chronic obstructive pulmonary disease, cancer and cardiovascular disease. The cytotoxicity of cigarette smoke is well documented, but the definitive mechanism behind its toxicity remains unknown. Ingredients in cigarette smoke are known to deplete intracellular glutathione (GSH), the most abundant cellular thiol antioxidant, and to cause oxidative stress. In the present study, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
1
23
3
Order By: Relevance
“…[19][20][21] These carbonyl compounds rapidly react with intracellular GSH and form their corresponding adducts, thereby depleting cellular GSH 4,22) and leading to cell damage. 4,22,23) In addition, it has been reported that a substantial amount of GSH in epithelial cells exposed to the gaseous phase of cigarette smoke is irreversibly modified to the GSH-ACR adduct (m/z 364) and GSH-CA adduct (m/z 378) by direct infusion mass spectra of the cell lysate, but the GSH-MVK adduct (m/z 378) and GSH-CA adduct are not separated. 7) Furthermore, it has been reported that the GSH-ACR and GSH-CA adducts can be detected in airway epithelial cells exposed to cigarette smoke, although the rela- tive yields were limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[19][20][21] These carbonyl compounds rapidly react with intracellular GSH and form their corresponding adducts, thereby depleting cellular GSH 4,22) and leading to cell damage. 4,22,23) In addition, it has been reported that a substantial amount of GSH in epithelial cells exposed to the gaseous phase of cigarette smoke is irreversibly modified to the GSH-ACR adduct (m/z 364) and GSH-CA adduct (m/z 378) by direct infusion mass spectra of the cell lysate, but the GSH-MVK adduct (m/z 378) and GSH-CA adduct are not separated. 7) Furthermore, it has been reported that the GSH-ACR and GSH-CA adducts can be detected in airway epithelial cells exposed to cigarette smoke, although the rela- tive yields were limited.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we revealed that MVK has a fairly stronger cytotoxicity than CA in mouse melanoma cells. 4) This phenomenon can be explained by the fact that aldo-keto reductases in the cells are more sensitive to the GSH-CA adduct than the GSH-MVK adduct, although further study is needed to elucidate such differences in the cytotoxicity of α,β-unsaturated carbonyls in cigarette smoke.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Glutathione adduct formation is known as a major cellular defense mechanism against acrolein and MVK . When we examined the levels of total and reduced glutathione (GSH), they were significantly decreased in Nox1 ‐disrupted clones (Fig.…”
Section: Resultsmentioning
confidence: 99%